Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening Pada PT. Sutan Kasim - Mohammad farhan; Muhammad fikri ramadhan; Jhon veri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of leadership style and work discipline on employee performance through work motivation as an intervening variable at PT. Sutan Kasim Padang. Employee performance is an important factor in supporting the achievement of company objectives, especially in the distribution and automotive workshop sector which requires high effectiveness and productivity. This research employed a quantitative approach using a survey method by distributing questionnaires to all employees of PT. Sutan Kasim Padang. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results indicate that leadership style and work discipline have a positive and significant effect on work motivation. In addition, leadership style, work discipline, and work motivation also have a positive and significant effect on employee performance. Work motivation is proven to mediate the relationship between leadership style and work discipline on employee performance. This study is expected to provide managerial implications in improving employee performance through effective leadership and work discipline.